دور التسويق الحسي في الاجهزة المحمولة على القرار الشرائي للمستهلك في قطاع الملابس في فلسطين لعام 2021 - قفيشة, اسراء; طرايرة, ايمان; الفلاح, سيرين; الشرباتي, ميس (جامعة بوليتكنك فلسطين - تسويق الكتروني, 2021)
تواجه عملية شراء المالبس عبر االنترنت صعوبات ومشاكل تتمثل في العزوف عن الشراء عبر االنترنت ألسباب تتعلق بالتخوف من التجربة وانخفاض مستوى الثقة. ويهدف البحث الى ايجاد حلول لهذه المشاكل بالتعرف على اسبابها واقتراح نمو ذج لهذا الغرض مدعما بتقنيات الواقع المعزز وتطبيقات المحمول في اطار التسويق الحسي بما يتناسب مع قطاع المالبس واالجهزة المحمولة. واعتمدت الدراسة على دراسات سابقة متعددة واستهدفت المستهلكين الفلسطينيين في قطاع المالبس من خالل استخدام اداتين لجمع البيانات هما االستبانة و المجموعة البؤرية، و اعتمد المنهج الوصفي والمنهج االستداللي في تحليل البيانات واستخالص النتائج، التي بينت الدور االيجابي للو اقع المعزز وزيادة ثقة المستهلك والتغلب على مخاو فه من عدم مطابقة المالبس للصورة اضافة لتقليل المرتجع وغيرها من العوامل، ليكو ن نقطة انطالق لتوسيعه وتعميمه . وتوصي الدراسة بتبني الواقع المعزز في تطبيقات البيع عبر االنترنت والعمل على النموذج المقترح . عالميا الحقا ABSTRACT This study is conducted due to the existing problems regarding online clothes shopping in Palestine which include: The reluctance of the majority of consumers to buy their clothes online, and their lack of trust in the quality of actual commodity specifications. Therefore, it presents solutions to the major problems that face online shoppers. The study mainly suggests adding latest technological methods to the shopping experience which can solve problems for the seller and the consumer. It also depends and builds upon previous studies regarding Palestinian consumers of the clothing sector. The study authors make use of two research methods which are questionnairing and focus group. In addition to descriptive and indicative approaches to achieve the study purposes. The study results emphasize on the efficacy of augmented reality in increasing consumers' trust to overcome the fear of non-conformity of the virtually presented pictures of items and their reality. Augmented reality also proved to help in reducing the number of returned items and other problems. The study also tackles the role of sensory marketing in clothing sector that affect the local Palestinian consumer. Finally, the study presents a guide for clothes trading companies that sell online and the companies that intend to. This can help in increasing their chances of success and distinguishability
no of pages 72 , تسويق الكتروني 2021
Keywords: التسويق الالكتروني; القرار الشرائي